Comparative Analysis of Quercetin and Taxifolin Interaction with Human Telomeric G-quadruplex DNA Hybrid form based on Molecular Dynamic Simulations - G. V. Chilingaryan (ՀՀ ԳԱԱ հրատ.)
G-quadruplex stabilizing ligands demonstrated their capability to decrease cell growth in vitro and in vivo cancer models. After more than a decade of investigations aimed at targeting telomeric G-quadruplexes, the development of G-quadruplex-based binding ligands has progressed slowly with only one candidate making it to clinical trials. The most urgent problems are the lack of high-resolution structural data for many G-quadruplex forms and small molecules’ low selectivity. In vitro և in vivo քաղցկեղային մոդելներում Գ-քվադրուպլեքսներ կայունացնող լիգանդները ցուցաբերում են բջիջների աճի նվազեցման ունակություն: Ուսումնասիրությունները, կապված Գ-քվադրուպլեքսներ կապող լիգանդների հետ, դանդաղ ընթացք են ունեցել, և միայն մեկ միացություն է հասել կլինիկական հետազոտությունների փուլի: Դրա հիմնական պատճառներն են բազմաթիվ Գ-քվադրուպլեքսների բարձր ճշգրտրտության կառուցվածքային ձևերի վերաբերյալ տվյալների տեղեկատվության բացակայությունը և լիգանդների ցածր ընտրողականությունը: G-квадруплекс стабилизирующие лиганды проявляют цитотоксичность в отношении роста раковых клеток в in vivo и in vitro моделях. В результате десятилетних исследований взаимодействия низкомолекулярных лигандов с G-квадруплексными структурами было выявлено всего одно соединение, достигшее клинических испытаний. Основными причинами этого являются отсутствие структурных данных высокого разрешения множества G-квадруплексных форм, а также низкая селективность исследуемых лигандов.
Keywords: Biology; Biochemistry; Biotechnology